INVESTIGATION OF SANITARY-HYGIENIC CHARACTERISTICS OF MULTILAYER POLYMER FILMS USED FOR VACUUM PACKAGING MODIFIED BY NATIVE ANTIMICROBIAL COMPONENTS - O. B. Fedotova; D. M. Myalenko (Теория и практика переработки мяса, 2016)
The results of the research works related to investigation of sanitary-hygienic characteristics of multilayer polymer film materials where the inner layer contacting directly with food product is modified by native antimicrobial components.